Efektivitas Rekayasa Lalu Lintas melalui Program Penambahan Lajur Khusus Sepeda Motor di Kota Surabaya - Rachmat Sumekar (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2016)
This study aimed to describe the effectiveness of traffic engineering was conducted by the Surabaya City Government in terms of the use of special lanes motorcycle in Darmo Street, Surabaya. This research used descriptive qualitative. Sources of primary data were collected through the interview method to the Transportation Department in Surabaya City which is connected with the Sub-Directorate of Safety Management and sub field of traffic. The results showed that first, implementation of the use of special lanes motorcycle was proved to decrease jam and provide a positive influence on the smooth traffic. Second, road performance such as Raya Darmo Surabaya Streer tended to have a positive value and stable. It is evidenced by the use of Raya Darmo Street by bikers still rising. Third, some things were still an obstacle for motorcyclists on some streets in Surabaya, such as in Raya Darmo Street: a) there is no special lane U-turn for motorcycles, b) there were no sanctions and threats for motorcyclists didn't use special lanes motorcycle. c) Lack of lighting, markings and traffic signs, d) It has not been the presence of a special officer to supervise the special lanes motorcycles, e) there is no rule speed limit for motors, f) there is no barrier strip permanently between lanes of motorcycles with another lane.